Sensitivity of material failure to surface roughness: A study on titanium alloys Ti64 and Ti407. (15th February 2021) - Sneddon, Scott; Xu, Yang; Dixon, Mark; Rugg, David; Li, Peifeng; Mulvihill, Daniel M.
Abstract: The relationship between material failure and surface roughness has been investigated using two titanium alloys: Ti64 and the more ductile Ti407. Three surface types were created (polished, sandblasted and scratched) with instances spanning a wide range of average roughness. The surfaces were tested in three-point bending with the imparted roughness on the tensile under-surface of a rectangular beam specimen. Results showed failure of Ti64 to be highly sensitive to both magnitude and orientation of roughness. High roughness in the maximum tensile stress direction (and scratch like features perpendicular to this direction) were most detrimental. Thus, strain-to-failure (and work-to-failure) in Ti64 dropped off significantly with increasing surface roughness in the tensile direction. Finite element modelling of the test indicated that cracks initiate at zones of high plastic strain at the tips of roughness valleys due to high local surface curvature. Thus, roughness can be considered as a series of blunt crack-like features where larger crack tip curvature induces greater likelihood of crack propagation. Contrastingly, the mechanical response of Ti407 was insensitive to surface roughness owing to its significantly greater ductility. Thus, designers need to be aware of the sensitivity of failure of particular materials to surface roughness. The insensitivity of Ti407 is advantageous, but the sensitivity of failure to surface roughness in a material like Ti64 is potentially serious if not properly accounted for. Graphical abstract: Unlabelled Image Highlights: Investigates the effect of surface finish on failure behaviour of two key aerospace titanium alloys: Ti64 and Ti407. Failure strain (and work-to-failure) in Ti64 is highly sensitive to both magnitude and orientation of surface roughness. High roughness in max tensile stress direction (& scratches perpendicular to this direction) were most detrimental. Cracks initiate at zones of high plastic strain at tips of roughness valleys corresponding to high local surface curvature. Ti407 was insensitive to surface roughness (even up to Ra = 20 μm) owing to its significantly greater ductility.